АСПЕКТИ УГОРСЬКО-УКРАЇНСЬКОГО ПОЕТИЧНОГО ПЕРЕКЛАДУ (НА МАТЕРІАЛІ ПЕРЕКЛАДІВ ЮРІЯ ШКРОБИНЦЯ). - ТАЛАБІРЧУК, Оксана (Alfred Nobel University Journal of Philology / Vìsnik Unìversitetu ìm. A. Nobelâ: Serìâ Fìlologìčnì Nauki, 2024)
The article addresses matters related to the peculiarities of Hungarian-Ukrainian poetic translation. It was noted that the quality, complexity and overall mastery of literary translation largely depend on the translator’s artistic personality, i.e., their knowledge, skills, and creativity. In our opinion, Yurii Shkrobynets was the one to perform the highest quality poetry translations in the field of poetic Hungarian-Ukrainian translation. During half a century of translation experience, he performed translations from Old Ukrainian, Czech, Slovak, German, Hungarian, Ossetian and Komi languages into Ukrainian, as well as from Ukrainian into Hungarian. The most significant portion of his translation heritage consists of translations of belletristic from Hungarian into Ukrainian, particularly these are 24 separate editions of both prose and poetic texts, and numerous poems, printed in periodic magazines and collections. Ukrainian translations of poetry by Yurii Shkrobynets are distinguished by linguistic richness and stylistic mastery, which can be seen in the way how all the structural features of the original work were preserved. The article’s topicality is determined by the insufficient research of both the theoretical issues of Hungarian-Ukrainian poetic translation, which require more thorough coverage within the framework of the partial theories of translation (in particular, it is of high importance to identify and describe different types of equivalents at the lexical, grammatical, and stylistic levels), and the translation principles and the translation concept by Yurii Shkrobynets. This [research] will contribute to the development of knowledge, skills and abilities that are necessary for a today’s Hungarian-Ukrainian translator. The purpose of the article is to trace and analyze the theoretical and practical aspects of poetic Hungarian-Ukrainian translation based on the literary translations by Yurii Shkrobynets. In order to achieve this purpose, the following objectives were set: 1) to outline the principal cultural and worldview patterns of Yurii Shkrobynets’ artistic personality; 2) to trace the distinguishing linguistic and stylistic differences between the Hungarian and Ukrainian languages and the difficulties they cause in terms of literary translation; 3) to identify and analyze the translation principles of Yurii Shkrobynets in order to highlight his individual style of poetic translation; 4) to find and examine the lexical-grammatical transformations used by Yurii Shkrobynets within the literary translation framework, using Janos Arany’s poem ‶Toldi″ in his translation as an example. In addition to general scientific methods of analysis, the following methods of analysis are used: synthesis and generalization of the material, the cultural-historical method, the method of comparative analysis of original and translated texts, and linguo-poetic analysis. It was proved that, despite the significant differences between the Hungarian and Ukrainian languages, it is possible to make such a professional literary translation can indeed reproduce the original work’s system of images and associations in full. Neither significant language differences nor national versification systems and related rhyming features become an obstacle, if the translator is well knowledgeable of them. The article investigates that the creative personality of Yurii Shkrobynets was formed under the influence of both Ukrainian and Hungarian cultures, the synthesis of which constitutes a part of the translator’s worldview. The profound understanding of cultural peculiarities and literary traditions that form both Ukrainian and Hungarian belletristic, as well as a perfect command of two languages contributed to the development and skills sharpening of Yurii’s talent for translation. It was proved that the translator had his own aesthetic preferences, and therefore, he introduced works into the Ukrainian cultural polysystem that primarily resonated with his own worldview and cultural values. The translation concept of Yurii Shkrobynets was formulated by himself in his article “My duelling with Toldi”, which became a resume of the following main ideas of his translation activity: 1) to translate exclusively from the original; 2) to keep faith in the original in such a way that the translated text affects a reader in the same way as the original; 3) as close as possible to deliver both content and formal components of the work in such a way that the adherence to the form does not cause damage to the contents; 4) to select the appropriate means of the Ukrainian language for the linguistic and stylistic features of the original text. A comparative analysis of the Hungarian poem “Toldi” by J. Aran and the translation performed by Yurii Shkrobynets, which is considered one of his best achievements, showed the translator’s strict adherence to his own translation concept. Despite the fact that the Hungarian language is not related to the Ukrainian language and there are significant lexical and grammatical differences, Yurii Shkrobynets managed to produce such professional translations of Hungarian poetry into Ukrainian that they were barely recognized as translations. The translator selects such kinds of expressions, phrases and lexicons which fully reflect and depict the cultural concepts of the Ukrainian language. However, it does not damage the original because the translator saves the key elements of the Hungarian linguistic culture. Yurii Shkrobynets, in his translation, uses a dialectal vocabulary of the Ukrainian language, tropes (namely, epithets, comparisons, metaphors), and phraseological units, which are primarily attributed to Ukrainian folklore. By means of lexical transformations, he transfers the meaning of the original text in such a way that the translation does not lose its essence, as far as the situation described by the original author and the translator is identical and is different only by means of its expression. We believe that the translation transformations applied by Yurii Shkrobynets, like full and partial replacement of word forms, complete reconstruction, rearrangement, omission, concretization, generalization, and transcoding of proper names and titles are well founded and caused primarily by the syntactic features of Hungarian and Ukrainian languages, as well as significant grammatical differences in general. Additionally, the translator could not manage to reproduce the poetic imagery of the original work and preserve its rhyming features without the usage of complex both lexical and grammatical transformations. Furthermore, the translator’s own poetic talent is worthy of being noted as it is expressed in neologisms and creative artistic translation of the individual original author’s features of the source text. Yurii Shkrobynets skillfully reproduces the features of the Hungarian versification and successfully matches with the equivalents to phraseological units and non-equivalent vocabulary. Altogether, these principles lead to the formation of a high-quality and adequate literary translation.